2017
DOI: 10.24036/voteteknika.v5i2.8490
|View full text |Cite
|
Sign up to set email alerts
|

Analisa Kepuasan Pengguna Aplikasi E-Xamp Editor Sebagai Aplikasi Ujian Sekolah Berbasis Komputer Di SMKN 3 Pariaman Menggunakan Metode End User Computing Satisfaction (Eucs) Yang Diperluas

Abstract: This study aims to evaluate the satisfaction of System e-Xamp Editor users in SMKN 3 Pariaman. The evaluation was conducted based on the perception of the end user by using End-User Computing Satisfaction (EUCS) model. EUCS Model has 6 factors i.e. content, accuracy, format, ease of use timeliness and flexibility, these 6 factors used as independent variable to evaluate e-Xamp editor user satisfaction in SMKN 3 Pariaman. This research using questionnaire as a primary data as well as scientific journals, refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
2
0
0
Order By: Relevance
“…Therefore, some users feel that the application provides benefits both in terms of complete services and in terms of new knowledge gained. This research supports research that has been done previously by Anesa et al (2017) where the content has a significant effect on user satisfaction of an information system. According to Anesa et al (2017), It was revealed that e-Xamp user satisfaction depends on e-Xamp's ability to provide benefits in the form of complete, quality and available information when needed during computer-based school exams.…”
Section: Influence Of Content On User Satisfaction Of Dukcapil Applic...supporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, some users feel that the application provides benefits both in terms of complete services and in terms of new knowledge gained. This research supports research that has been done previously by Anesa et al (2017) where the content has a significant effect on user satisfaction of an information system. According to Anesa et al (2017), It was revealed that e-Xamp user satisfaction depends on e-Xamp's ability to provide benefits in the form of complete, quality and available information when needed during computer-based school exams.…”
Section: Influence Of Content On User Satisfaction Of Dukcapil Applic...supporting
confidence: 89%
“…This research supports research that has been done previously by Anesa et al (2017) where the content has a significant effect on user satisfaction of an information system. According to Anesa et al (2017), It was revealed that e-Xamp user satisfaction depends on e-Xamp's ability to provide benefits in the form of complete, quality and available information when needed during computer-based school exams. The same is true for users of the Dukcapil application, where user satisfaction depends on the application's ability to provide complete, quality and useful services.…”
Section: Influence Of Content On User Satisfaction Of Dukcapil Applic...supporting
confidence: 89%